W jaki sposób lekcja języka ojczystego może przyczynić się do rozwoju wielojęzyczności uczniów? - Łyp-Bielecka, Aleksandra (Neofilolog, 2012)
Effective teaching and learning of foreign languages is one of the main objectives of institutionalized school education. The high level of learners language awareness enhances the development of multilingualism. The article presents selected means of rising language awareness during native language lessons in Polish schools.